(untitled) (Italian Journal of Public Health, 2011)
Background: Male circumcision is a removal of the foreskin of the glans penis. There are medical, ritual and religious reasons for male circumcision. The purpose of this study is to explore the current practices, perceptions, future recommendations and health seeking behavior during and after performing male circumcision in a Muslim community of western Nepal. Method: A total of 64 households were sampled by a simple random sampling method. Information was collected using semi-structured questionnaires and focus group discussions. Result: Circumcision was practiced among all Muslim households and the main reason was religious rite and ritual. It was the traditional circumciser, locally known as hazam, who circumcised all male children in the community. Interestingly, in only 5 % of the household children had been circumcised using modern medicines. The rest of the households, i.e. 95%, relied on traditional healing systems, the use of local herbs and homemade ointments (mainly the suspension of ghee and ash). A Non-sterilized knife was the main surgical instrument used during circumcision. The wound healing after circumcision was much longer, even up to 90 days or more. Conclusions: Circumcision is a practice that is still largely carried out outside the domain of the formal health care system in this community. It demands a design of service delivery models from health policy makers in the Ministry of Health, thus bringing circumcision within formal health care systems in those communities. It deserves an urgent attention to provide safe, culturally acceptable and sustainable services from health institutions.